Buckling Patterns of Graphene–Boron Nitride Alloy on Ru(0001). Issue 18 (1st October 2015) - Kutana, Alex; Goriachko, Andrii; Hu, Zhili; Sachdev, Hermann; Over, Herbert; Yakobson, Boris I.
Abstract : Buckling nanopatterns of monoatomic layer 2D materials on metal substrates attract significant attention due to their rich interface morphology affecting electronic applications. An experimental–theoretical study of a 2D boron–nitrogen–carbon (B x /2 N x /2 C1− x ) alloy on a Ru(0001) surface is conducted and a profound relation between the composition x and the degree of buckling is discovered. Experimentally, real carbon–boron–nitrogen alloys on the Ru(0001) surface are demonstrated and various morphologies of pure and mixed compounds are shown. Density functional theory calculations are further carried out using the supercells of graphene, hexagonal boron nitride (h‐BN), and random BNC on Ru(0001), as well as Monte Carlo simulations for elucidating the kinetics of their growth. The results show that unlike pure compounds (h‐BN or C), the carbon–boron–nitrogen mix on Ru(0001) mostly exists in an uncorrugated form, thus greatly improving the interface contact. The likely cause of the diminished corrugation is a softening of bond angular interactions in the alloy relative to the pure phases. Abstract : A 2 D boron–nitrogen–carbon (BNC) alloy on a Ru(0001) surface is experimentally and theoretically studied, and a profound relation between the composition and the degree of buckling is discovered. BNC on Ru(0001) exists in a mostly uncorrugated form. The likely cause of diminished corrugation is a softening of bond angular interactions in the alloy relative to the pure phases.